Gejala Patologi Birokrasi Pemerintah Desa Dan Pengaruhnya Terhadap Keberhasilan Pengelolaan Dana Desa - S, Nur Lazimatul Hilma; Ishak, Parmin (Gorontalo Accounting Journal, 2021)
This study purposed to analyze the indication of bureaucratic pathology of the village government and its effect on the success of village fund budgeting management by applying the variable dysfunction of bureaucracy and mal administration as independent variables and accountability as the dependent variable.This research is applying descriptive analysis research methods and multiple regression with 98 participants from the staff of theÂ  village offices in Wonosari sub district. As the results, this study shows that simultaneously dysfunction of bureaucracy and mal administration have a significant effect on accountability, while partially the variable Disfunction of bureaucracy does not have a significant effect. On the other hand, mal administration has a significant effect on the accountability of the village government.